Overlapping borders. Images of East Belgium as a transcultural area in contemporary East Belgian literature - Beck, Philippe; Penné, Lesley (Oxford German Studies, 2019)
„In this contribution, we discuss how the East Belgian authors Hannes Anderer, Freddy Derwahl and Leo Wintgens represent history, borders and multilingualism in their novels. These contemporary authors have understood that coming to terms with the past is an important aspect in developing a genuine East Belgian collective identity. Furthermore, the multiple borders (with Germany, the Netherlands and Luxembourg) and the co-existence of several languages in this region have become constitutive of collective self-understanding, also with regard to the construction of a region-specific cultural memory. Finally, we show the narrative strategies used in the novels Unterwegs zu Melusine (2006), Bosch in Belgien (2006) and Wege aus Sümpfen. Roman einer Grenzlandschaft Teil I (2001) and Teil II (2006) in order to bring to bear the relation between minority and majority culture by recurring to imagology.“
Keywords: Annexion; Geschichtsbild; Geschichtsschreibung; Kulturelle Identität; Mehrsprachigkeit; Schriftsteller; Staatsgrenze

„“L’identité des Belges germanophones est une non-identité“. Quelques réflexions à propos de publications récentes sur l’histoire de la Communauté germanophone de Belgique - Brüll, Christoph (BEG-CHTP, 2009)
Keywords: Deutschsprachige Gemeinschaft; Kulturelle Identität; Nationalbewusstsein; Ostbelgien; Regionale Identität

Luxemburg - ein Teil des deutschen Reiches? Zur Kontinuität der landes- und volkskundlichen Kulturraumforschung und ihr Verhältnis zur kulturellen Identität Luxemburgs im 20. Jahrhundert - Freckmann, Klaus (Griff nach dem Westen. Die „Westforschung“ der völkisch-nationalen Wissenschaften zum nordwesteuropäischen Raum (1919–1960), 2003)
Keywords: Kulturelle Identität; Kulturraumforschung; Westeuropaforschung